2011
DOI: 10.1186/2191-1991-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Considerations about the effectiveness and cost effectiveness of therapies in the treatment of hyperphosphataemia

Abstract: Because of an elevated serum phosphate level, patients who suffer from chronic kidney failure frequently tend to have cardiovascular calcification and are therefore exposed to a higher probability of a fatal event. Phosphate binders are able to reduce these negative effects. Currently, there are primarily two groups of phosphate binders (calcium-containing and calcium-free phosphate binders) which are considered to be almost equally effective in terms of binding of free phosphate. There are, however, a few dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
(29 reference statements)
2
18
0
Order By: Relevance
“…Active transport such as walking and cycling provides an opportunity to incorporate frequent physical activity into daily living, which could help people achieve recommended levels of physical activity. Moreover, various evidence of a positive association between active transport and health outcomes has been published [20, 4751]. For example, a recent systematic review [52] summarised evidence of the health benefits of cycling and reported a strong inverse relationship between commuter cycling and all-cause mortality, cardiorespiratory fitness, cancer mortality and morbidity, and a clear positive dose-response relationship between the amount of cycling and body fitness, and incidence of overweight and obesity decrease.…”
Section: Evidence Of Potential Benefits Of Promoting Alternative Tmentioning
confidence: 99%
“…Active transport such as walking and cycling provides an opportunity to incorporate frequent physical activity into daily living, which could help people achieve recommended levels of physical activity. Moreover, various evidence of a positive association between active transport and health outcomes has been published [20, 4751]. For example, a recent systematic review [52] summarised evidence of the health benefits of cycling and reported a strong inverse relationship between commuter cycling and all-cause mortality, cardiorespiratory fitness, cancer mortality and morbidity, and a clear positive dose-response relationship between the amount of cycling and body fitness, and incidence of overweight and obesity decrease.…”
Section: Evidence Of Potential Benefits Of Promoting Alternative Tmentioning
confidence: 99%
“…In these reviews, however, the cost‐effectiveness of first‐line sevelamer and that of LC versus sevelamer were not established . CA combined with magnesium carbonate was suggested by Plagemann et al . as a cost‐effective first‐line therapy.…”
mentioning
confidence: 99%
“…as a cost‐effective first‐line therapy. However, this review did not include any full economic evaluation of this combination and was funded by the pharmaceutical industry. None of these reviews adopted a systematic methodology or critically appraised the quality of included studies.…”
mentioning
confidence: 99%
See 2 more Smart Citations